Women, Drug use and Imprisonment. Intersectional Approach - de Miguel Calvo, Estibaliz (Política y Sociedad, 2016)
Research on women prisoners and drug use is scarce in our context and needs theoretical tools to understand their life paths. In this article, I introduce an intersectional perspective on the experiences of women in prison, with particular focus on drug use. To illustrate this, I draw on the life story of one of the women interviewed in prison, in order to explore the axes of inequality in the lives of women in prison. These are usually presented as accumulated and articulated in complex and diverse ways. The theoretical tool of intersectionality allows us to gain an understanding of the phenomenon of women prisoners who have used drugs. This includes both the structural constraints in which they were embedded and the decisions they made, considering the circumstances of disadvantage in which they were immersed. This is a perspective which has already been intuitively present since the dawn of feminist criminology in the English-speaking world and can now be developed further due to new contributions in this field of gender studies.